Investigation of dynamics and its factors of interest rates in lithuania in 1994-2006 - Jasienė, Meilė; Čapskas, Giedrius (Business: Theory and Practice, 2008)
Interest is the amount paid by a borrower to a lender in exchange for the use of the lender’s money for a certain period. Interest rate is the price of lending money. Investigation of interest rates dynamics and its factors can be carried out according to three main theories: unbiased expectations, liquidity preference, and market segmentation theory. Interest rates’ factors are divided into three groups: economical, political, and social factors. Lithuanian banks’ loan and time deposit interest rates analysis shows, that there were decreasing interest rates and net interest margin in the period of 1994–2006. The main reason, which influenced interest rates to fall, was decreasing price level. Crisis in Russia caused sharp increase in loan and time deposit interest rates in 1999. On the other hand, competition in the loan and time deposit markets became more severe and it led to a decrease in interest rates. Economic cycle in Lithuania and general interest rates level have the opposite relation, which was confirmed by correlation analysis. As a result of analysis the authors make the interest rates forecast. As history of last years shows – ECB will increase the minimum bid rate on the main refinancing operations within limits of 0.25–0.5 p. p. This would effect interest rates level in Lithuania from 0.4 to 0.7 p.p. in 2007. For the reason that inflation in fast growing country will reach 4.5 percent (forecast), real interest rate of deposits in most banks will be negative.Article in Lithuanian.Palūkanų normų kaitos ir jos veiksnių tyrimas Lietuvoje 1994–2006 m.Santrauka. Šio straipsnio tikslas – pamėginti ištirti viso Pohiper infliacinio laikotarpio palūkanų normos dinamiką, atlikti jos periodizaciją, nustatyti buvusius dėsningumus, išskirti pagrindinius veiksnius. Tai galėtų būti naudinga prognozuojant palūkanų normų pokyčius ateityje, ypač kartojantis ekonomikos ciklui. Palūkanų normos vaidina svarbų vaidmenį skatinant verslo aktyvumą. Skolinimo sandoriuose nustatomos palūkanų normos. Bankai moka palūkanas už indėlius ir gauna palūkanas už suteiktas paskolas. Palūkanų normų kaitos ir jos veiksnių analizė leidžia geriau pažinti palūkanų normos susiformavimo mechanizmą ir ją prognozuoti. Straipsnyje aptariami palūkanų normų analizės teoriniai pagrindai, analizuojama palūkanų normų kaita Lietuvoje 1994–2006 m. laikotarpiu, išskiriami penki laiko-tarpiai ir jiems būdingi palūkanų normos dinamikos dėsningumas, nustatomi ir kiekybiškai įvertinami pagrindiniai veiksniai, darę įtaką palūkanų normų kaitai. Pamėginta pateikti palūkanų normų prognozę artimiausiam laikotarpiui.Reikšminiai žodžiai: palūkanų norma, infliacija, veiksniai, indėliai, paskolos, bankai.First published online: 19 Mar 2008